2021
DOI: 10.1097/md.0000000000024930
|View full text |Cite
|
Sign up to set email alerts
|

Effect of muscle training on dyspnea in patients with chronic obstructive pulmonary disease

Abstract: Background: Rehabilitation training is beneficial for patients with chronic obstructive pulmonary disease (COPD). This study was aimed at evaluating the efficacy of muscle training on dyspnea. Methods: We used 5 common databases for conducting a meta-analysis included PubMed, the Cochrane Library, Science Direct, Web of Science and Clinical Trials.gov, and eligible randomized controlled trials (RCTs) were included. The main results of include studies were dyspnea of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
1
9
0
5
Order By: Relevance
“…We did not find an improvement in the 6MWD, but we did observe a change in the Borg scale for the perception of dyspnea and fatigue. This variation was statistically significant in both groups, and mostly in the experimental group, in line with studies by other authors [ 37 ]. In addition, we noted an improvement in the mMRC scale in the HFOT group.…”
Section: Discussionsupporting
confidence: 92%
“…We did not find an improvement in the 6MWD, but we did observe a change in the Borg scale for the perception of dyspnea and fatigue. This variation was statistically significant in both groups, and mostly in the experimental group, in line with studies by other authors [ 37 ]. In addition, we noted an improvement in the mMRC scale in the HFOT group.…”
Section: Discussionsupporting
confidence: 92%
“…Respiratory muscle training (RMT) is a therapy used in several pathologies to improve respiratory capacity. There is evidence about the positive effect of RMT in patients with chronic obstructive pulmonary disease (COPD) (6), amyotrophic lateral sclerosis (ALS) (7), and COVID-19 (8)(9)(10). In addition to the effects obtained on respiratory capacity, studies have found how patients experience improvements in QoL.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise is one of the number of successful interventions improving the physical and psychological health of patients with different cancers (including lung cancer). 8 , 9 The perioperative management of patients with lung cancer includes cardiopulmonary rehabilitation; it can reduce symptoms and minimize cancer exacerbations. 8 , 9 Pulmonary rehabilitation can improve the exercise capacity and health-related quality of life of patients, and it reduces the presence of major symptoms like fatigue, dyspnea, depression, and others.…”
Section: Introductionmentioning
confidence: 99%